On-farm storage of livestock vaccines may be a risk to vaccine efficacy: a study of the performance of on-farm refrigerators to maintain the correct storage temperature - Paul D. Williams; Gustavo Paixão (BMC Veterinary Research, 2018)
Abstract Background Livestock vaccines (LV) are often stored on-farm, in a refrigerator (fridge), prior to use and little is documented about the storage conditions during this period. As the quality of a vaccine can be impaired by storage at an incorrect temperature, the present study aimed to evaluate the on-farm performance of farm fridges to maintain the correct storage temperature. From January to August 2014, temperature data loggers were placed on selected farm fridges used to store LV (n = 20) in South-West England. Results Temperature recording data was available from 17 of the 20 farms. Fifty-nine percent of farm fridges had at least one temperature recording above 8 °C, 53% had at least one recording below 2 °C and 41% at or below 0 °C. Internal fridge temperatures attained 24 °C and dropped to − 12 °C as an absolute maximum and minimum respectively. Fridges tested spent an average of 16% of the total time recorded above 8 °C. Time of the year significantly influenced the percentage of time above 8 °C. External and internal temperatures were found to be positively correlated (p < 0.001). Statistical significant differences in internal and external temperatures were found between March and August. Conclusions The majority of fridges in this study would have failed to keep any stored LV within the recommended storage temperature range. If LV are going to be stored on-farm prior to use, then urgent improvements in this part of the cold-chain are required in order to insure vaccine efficacy is not compromised.